THE IMPACT OF COVID-19 PANDEMIC ON POVERTY IN JAMBI PROVINCE - Vivi Herlina; Enny Sestriyenti (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
This study examined the impact of the COVID-19 pandemic on poverty in Jambi Province. The independent variables were the human development index, unemployment rate, population, GDRP, and Covid19. This paper used panel data from the Central Bureau of Statistics Republic of Indonesia, as the cross-section data are all regencies in Jambi Province for 2017 and 2020. The first step was an appropriate model selection and analyzed by F-test, t-test, and determinant coefficient. Results from the analysis show that the best model is the random effect. The F-test stated that all of the independent variables affect the poverty percentage simultaneously. Meanwhile, the t-test found that only the human development index variable has a significant effect.